2021
DOI: 10.1016/j.asmr.2021.05.002
|View full text |Cite
|
Sign up to set email alerts
|

The Injury Rate in National Football League Players Increased Following Cancellation of Preseason Games Because of COVID-19

Abstract: Purpose: To investigate the injury rate in National Football League (NFL) athletes during the first 4 weeks of the 2020 NFL season. Methods: This study was a retrospective review of all NFL players who were placed on the injury report during the preseason and the first 4 weeks of the regular season from the 2016-2017 through the 2020-2021 NFL regular seasons. Players' dates of injury were cross-referenced with an absence of statistics from the respective games for which they were ruled out so as to ensure accu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
46
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(52 citation statements)
references
References 22 publications
2
46
0
Order By: Relevance
“…A recent study by Baker et al 4 identified a significantly increased proportion of general injuries in the NFL in the first 4 weeks of the regular season in 2020 relative to prior years. Our study corroborates these findings over a longer time frame and also adds that later months in the season did not see increased rates of injuries for ACL tears specifically.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent study by Baker et al 4 identified a significantly increased proportion of general injuries in the NFL in the first 4 weeks of the regular season in 2020 relative to prior years. Our study corroborates these findings over a longer time frame and also adds that later months in the season did not see increased rates of injuries for ACL tears specifically.…”
Section: Discussionmentioning
confidence: 99%
“…17 For preseason games, AEs were estimated for each season, using 90 players on the roster for the first 3 weeks of preseason games (including the Hall of Fame Game) and 75 players for the 4th week of preseason games. 4 For in-season games, total AEs were calculated using the regular season plus postseason games, 53-man active roster, and 32 NFL teams (Table 1). While the 2020 season allowed for teams to add up to 1 to 2 additional players from the practice squad to the active roster (to a 54- or 55-man roster), 17 this was not used in calculations due to the variability in usage by teams throughout the season and because these players reverted to the practice squad after games for up to maximal 2 games for the season per player.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…19 The same effect may have been seen as athletes returned to sports after COVID-restrictions were lifted, for example, two early studies on NFL players suggested that an abrupt return to sport may have contributed to an increased rate of on-field injuries. [20][21] With quarantine regulations, we expect many patients were deconditioned when they returned to play. Children and adolescents in particular may have been at increased risk of injury from COVID restrictions, due to the combination of deconditioning and changes in body habitus that occurred during their "off season."…”
Section: Discussionmentioning
confidence: 99%
“… 7 The NFL injury registry showed that the injury numbers in the 2020–2021 season, with incomplete preseason preparation and cancelled practice matches, were higher than in the 3 years before with normal season preparation. 8 In the German Bundesliga, match-related injury rates increased from 0.27 to 0.84 after the first strict COVID-19-related lockdown period. 9 How sports participation restrictions relate to sports injury rates during the pandemic remains yet largely unknown.…”
Section: Changes In Sports Participation and Injurymentioning
confidence: 99%